Field evaluation of specimens from a corn collection for resistance to Helminthosporium turcicum Pass and Fusarium moniliforme Scheldon - Telichko Ol’ga; Belova Tat’yana; Syrmolot Oksana; Lastushkina Elena (E3S Web of Conferences, 2024)
The paper presents research data on the spread and development of the main fungal pathogens of corn. Corn holds a prominent place among the other grain crops grown in Primorsky kray. Corn is susceptible to more than 120 different pathogens. Helminthosporium turcicum Pass and Fusarium moniliforme Scheldon cause significant damage to zea mays plants under the conditions of the south of the Russian Far East. The research evaluated 148 corn genotypes. The progression degree of northern leaf blight ranged from 8 to 70% at the kernel milk stage depending on the specimen (the prevalence was 38-100%); the occurrence frequency of Fusarium ear rot varied within 0-90%. The conducted research resulted in the identification of genotypes with resistance to these pathogens. The following genotypes might be valuable for further breeding: S-1847, k-23428 B, k-24825, R-nj purple, k-22077, k-21477, S-430 V, MP-162-B, and varieties Sakharnaya and Indeiskaya krakhmalistaya.